Identificación de naproxeno sódico 550 mg en tabletas por espectroscopia infrarroja - Zavala Rios, Dilver Alexander (2019)
The purpose of this work was to identify 550 mg sodium naproxen in tablets by infrared spectroscopy, for which the Perkin Elmer-Spectrum TWO infrared spectrometer was used, with Fourier transform and universal refractive accessory, in the range of 450-4000 cm-1. one. As a study material, secondary standard (ES) of naproxen sodium, naproxen tablets 550 mg of an innovative drug (MI) and 13 multi-source drugs (MM) were used. Product specimens of the molecular vibration expressed in wave numbers were obtained, the molecular vibration for OH was a band between 3322 to 3447 cm -1 (ES, MI and MM), for the group C=O it was a signal of 1659-1671 cm-1 (MI and MM M1-M12), the aromatic double bond was 1630-1632 cm-1 (ES, MI and MM M1-M12), for the symmetric COO- 3 different signals 1542-1544 cm-1 were evidenced 1 (MI and MM M2, M3, M7-M12), 1555-1557 cm-1 (MM M4-M6) and 1584 cm-1 (ES and MM M1), this variation is an indicator of different IFAs and the COO- Asymmetric was between 1481-1486 cm-1 (ES, MI, MM M1-M12). The methyl group presented 2 flexion signals, the first between 1364-1369 cm-1 and the second between 1387-1389 cm-1 (ES, MI and MM M1-M12). The MM M13 signals did not correspond to sodium naproxen. It is concluded that the innovative medicine and M1 to M12 multi-source medicines correspond to sodium naproxen, with at least 3 different crystalline forms, also the M13 multi-source medicine does not correspond to sodium naproxen, being an adulterated product